2020
DOI: 10.1155/2020/1201923
|View full text |Cite
|
Sign up to set email alerts
|

Functionalized Metal-Organic Framework Catalysts for Sustainable Biomass Valorization

Abstract: Currently, pristine and functionalized metal-organic frameworks (MOFs) are introduced in heterogeneous catalysis for biomass upgrading owing to the specific texture properties including regular higher-order structure, high specific surface area, and the precisely tailored diversity. The purpose of this review is to afford a comprehensive discussion of the most applications in biomass refinery. We highlight recently developed four types of MOFs like pristine MOFs and their composites, MOF-supported metal NPs, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 76 publications
0
10
0
Order By: Relevance
“…Additional studies have shown that the activity of enzymes immobilized on MOFs is not affected by exposure to denaturing organic solvents, such as methanol, ethanol, dimethylformamide, and dimethyl sulfoxide. The enzymes immobilized on MOFs retain 100% of their initial activity, in contrast to free enzymes, which retain only up to 20% of their initial activity under the same denaturation conditions [48].…”
Section: Enzyme Stabilitymentioning
confidence: 99%
“…Additional studies have shown that the activity of enzymes immobilized on MOFs is not affected by exposure to denaturing organic solvents, such as methanol, ethanol, dimethylformamide, and dimethyl sulfoxide. The enzymes immobilized on MOFs retain 100% of their initial activity, in contrast to free enzymes, which retain only up to 20% of their initial activity under the same denaturation conditions [48].…”
Section: Enzyme Stabilitymentioning
confidence: 99%
“…Furthermore, the main support materials discussed (silica and carbon) are also cheap to obtain. , As we have established earlier, carbon supports arranged in a mesoporous structure, in particular the MOF structure, can improve the flow path and therefore the overall catalytic activity. However, mesoporous structures, especially if ordered in a specific way, such as MOF, are expensive to synthesize and therefore to apply in industry. ,, …”
Section: Challenges and Future Directionsmentioning
confidence: 99%
“…152 Furthermore, MOF has been used for CO 2 capture and separation. 238 By extension, MOF materials are more expensive to synthesize 239 and are not highly stable materials, 240,241 as compared to conventional catalysts such as Cu/ZnO/Al 2 O 3 . Therefore, additional consideration should be given toward modifying the structure and materials of the MOF-based catalysts to improve activity and stability.…”
Section: Promoter Combinationsmentioning
confidence: 99%
“…MIL-101(Cr) consisting of chromium oxide clusters and terephthalic acids are highly stable even in strong acid aqueous solutions because it is synthesized in a hydrofluoric acid medium [25]. In addition, MIL-101(Cr) material is characterized by high specific surface and easy exposure of acid sites [29].…”
Section: Introductionmentioning
confidence: 99%